Guía de capacitación para la creación de una caja común en el barrio Celen de la parroquia Gualel del cantón Loja - Paccha Márquez, Enma Marlene (2018)
The present investigation was developed in the neighborhood Celen of the GualelParish of the Loja canton, in the productive sectors of agricultural activities (agriculture and livestock), which evidenced an inadequate administration of the economic resources, according to information provided by the inhabitants of the sector, beforethis problem was raised the creation of a common fund that encourages Savings -Investment, and encourages the generation of productive activities, which contribute to overcome the precariousness in which in some cases affects these communities. For the development of the work qualitative research was used, using the technique of observation, interview and bibliographic information. As a result of the proposal, the Financial Education Training Guide for the participating population is presented, aimed at administering the economic and financial resources, becoming a useful tool that benefits both the individual and the foreigners and enhances their productive agricultural activities. be from the community. It concludes the importance of linking with societythrough academia for the training of vulnerable sectors such as the Celen neighborhood through the training provided that allowed the formation of a common box called Holy Spirit of Celen, the same receptara savings community and loans to members and their families that require these services as well as a permanent supply of monetary resources aimed at constant production and the generation of short-term income.